2016
DOI: 10.1186/s12967-016-0944-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-targeted TNFα and IFNγ inhibits orthotopic colorectal tumor growth

Abstract: BackgroundTumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ) were originally identified to show potent anti-tumor activity and immunomodulatory capability. Unfortunately, several clinical studies of relevant cancer therapy did not observe significant response in maximum tolerated dose whether given alone or in combination. We have identified a tumor vasculature homing peptide (TCP-1 peptide) which targets only the vasculature of colorectal tumors but not normal blood vessels in animals and humans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…Absence of either TNFR1 signalling or IFNγ signalling determined Tag‐specific Th1 cells to induce tumour dormancy or promote multistage carcinogenesis, which was another solid evidence supporting the co‐operative effects of TNFα and IFNγ in anti‐tumour treatment. Our recent study using tumour vasculature homing peptide TCP‐1 showed that targeted combination therapy with TCP‐1/TNFα and TCP‐1/IFNγ could remarkably inhibit orthotopic colorectal tumour growth by inducing tumour necrosis without causing significant systematic toxicity . The anti‐tumour effects of TNFα and IFNγ either using alone or in combination are summarized in Figure .…”
Section: Co‐administration Of Tnfα and Ifnγ In Anti‐cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of either TNFR1 signalling or IFNγ signalling determined Tag‐specific Th1 cells to induce tumour dormancy or promote multistage carcinogenesis, which was another solid evidence supporting the co‐operative effects of TNFα and IFNγ in anti‐tumour treatment. Our recent study using tumour vasculature homing peptide TCP‐1 showed that targeted combination therapy with TCP‐1/TNFα and TCP‐1/IFNγ could remarkably inhibit orthotopic colorectal tumour growth by inducing tumour necrosis without causing significant systematic toxicity . The anti‐tumour effects of TNFα and IFNγ either using alone or in combination are summarized in Figure .…”
Section: Co‐administration Of Tnfα and Ifnγ In Anti‐cancer Therapymentioning
confidence: 99%
“…Our recent study using tumour vasculature homing peptide TCP-1 showed that targeted combination therapy with TCP-1/TNFα and TCP-1/IFNγ could remarkably inhibit orthotopic colorectal tumour growth by inducing tumour necrosis without causing significant systematic toxicity. 100 The anti-tumour effects of TNFα and IFNγ either using alone or in combination are summarized in Figure 1. Our result emphasizes the therapeutic potential of co-administration of targeted TNFα and IFNγ for cancer treatment and the utility of TCP-1 peptide as a tumour-targeting agent in colorectal cancer.…”
Section: Theanti-canceractivityofifnγmentioning
confidence: 99%
“…In mouse models of highly aggressive mesenchymal CRC tumors, a potential synergistic effect was observed with the combination of a TGFR inhibitor with a PD‐1 checkpoint inhibitor , or with an agonistic OX40 mAb , which enhanced effector function and survival of activated T cells. The positive treatment outcome was associated with an expansion of tumor‐infiltrating effector CTLs and TH1 cells, enhanced antitumor T‐cell immunity , and a high tumor‐specific IFN‐ γ response . Alternative immunotherapeutic approaches to be explored in inflamed TGF‐ β ‐mediated mesenchymal tumors include pharmacological elimination of MDSCs or blockade of related immunosuppressive chemokine signaling circuits and pathways, as demonstrated in other malignancies with an immune‐evasive microenvironment .…”
Section: Strategy To Overcome the Acquire Immune Resistance In Crcmentioning
confidence: 99%
“…Factors secreted from cancer cells activate cells in the stroma, and then activated stromal cells stimulate cancer cells to proliferate and migrate [ 82 , 83 ]. Therefore, it might be possible to treat cancer by manipulating the cancer microenvironment [ 84 , 85 ]. Approaches aimed at manipulating stroma, such as through the introduction of IL2, IL12, or GM-CSF, appear to contribute to the success of gene therapy by nonviral vectors.…”
Section: Efficiency Of Gene Therapy With Nonviral Vectorsmentioning
confidence: 99%